Comparing Audit Quality of Big 4 and Non-Big 4 Auditors - PING, CHAO-WEN (2010)
In the first decade of the 21st centuries, there were many multinational corporations collapsed because of fraud. These scandals have induced concerns about audit quality even among the large international accounting firms. This study examines the quality of audit services in the Taiwanese audit market. Consistent with prior research, this paper treat audit quality as a dichotomous variable, and assume that Big 4 auditors are of higher quality than non-Big 4 auditors, as it is widely accepted that high-quality auditors are more likely to be able to constrain managers’ aggressive earnings management behaviour. Therefore, the proposed hypothesis of this Audit quality is captured by discretionary accruals that are estimated using the Cross-sectional version of the Jones Model. The sample consists of 1,390 firm year observations audited by Big 4 auditors and 346 firm year observations audited by non-Big 4 auditors. The T-statistic is employed to examine the hypothesis that international accountancy firms (the Big 4 auditors) provide better audit quality than other small auditors. The research result does not support the proposed hypothesis, clients of Big 4 auditors report higher amount of discretionary accruals than clients of non-Big 4 auditors.